Investigating pathogens of the gastrointestinal tract in sudden and unexpected death in infancy cases at the Tygerberg medico-legal mortuary, compared to an age-matched healthy control group. - Cupido, Danielle Tiffany (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.